2021
DOI: 10.3390/jcm10112364
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Albuminuria and the Kidney—Brain Axis

Abstract: Cognitive decline and kidney disease are significant public health problems that share similar characteristics and risk factors. The pathophysiology of the kidney–brain axis is not completely understood, and studies analysing the relationship between the biomarkers of kidney damage and cognitive impairment show different results. This article focuses on the epidemiological and clinical aspects concerning the association of albuminuria, a marker for endothelial dysfunction and microvascular disease, and cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Traditional risk factors for cognitive impairment in CKD include aging, female gender [ 9 ], education status, nonwhite ethnicity, diabetes mellitus [ 10 ], hypertension, and cardiovascular disease, which have been extensively reviewed recently [ 7 , 11 , 12 , 13 , 14 ]. Here, we will discuss the nontraditional risk factors in depth, including hyperhomocysteinemia, oxidative stress, low estimated glomerular filtration rate (eGFR), albuminuria, malnutrition, and inflammation (shown in Fig.…”
Section: Risk Factors Leading To Cognitive Impairment In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional risk factors for cognitive impairment in CKD include aging, female gender [ 9 ], education status, nonwhite ethnicity, diabetes mellitus [ 10 ], hypertension, and cardiovascular disease, which have been extensively reviewed recently [ 7 , 11 , 12 , 13 , 14 ]. Here, we will discuss the nontraditional risk factors in depth, including hyperhomocysteinemia, oxidative stress, low estimated glomerular filtration rate (eGFR), albuminuria, malnutrition, and inflammation (shown in Fig.…”
Section: Risk Factors Leading To Cognitive Impairment In Ckdmentioning
confidence: 99%
“…In fact, an 11-year follow-up study elucidated that albuminuria and microalbuminuria, as early markers of endothelial damage of the renal glomeruli, could help predict cognitive decline [8]. However, the intricate pathogenic relationship and exact and cardiovascular disease, which have been extensively reviewed recently [7,[11][12][13][14]. Here, we will discuss the nontraditional risk factors in depth, including hyperhomocysteinemia, oxidative stress, low estimated glomerular filtration rate (eGFR), albuminuria, malnutrition, and inflammation (shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Some hypotheses may link albuminuria with the pathogenesis of small cerebral vessels, which is related to the aggravation of cognitive impairment, but the specific pathological mechanism is unclear. [ 34 ] In summary, simultaneous treatment of the kidney and brain may be an important breakthrough in the treatment of PSCI using TCM techniques. At the same time, according to the results of this study, it is suggested that clinical workers can perform acupuncture with methods that nourish the kidney and marrow and perform rehabilitation treatment according to the different clinical symptoms and severity of PSCI at the same time to achieve the best therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…In people with diabetes, the pathophysiology of cognitive decline can involve several interrelated factors. Both hyperglycemia and hypoglycemia have detrimental effects on cognition [73]. There are few data on a putative beneficial effect on cognition of glycemia control, even though some interventions are known to improve kidney-related outcomes (e.g., albuminuria).…”
Section: Antidiabetic Agentsmentioning
confidence: 99%
“…Among them, pioglitazone, a synthetic ligand of peroxisome proliferator-activated receptors, and liraglutide, a GLP-1 receptor agonist, have shown neuroprotective effects by diminishing the cognitive decline in experimental and observational studies in humans [75,76]. Future clinical studies of antidiabetic agents and cognitive function might benefit from measuring albuminuria and kidney function [73].…”
Section: Antidiabetic Agentsmentioning
confidence: 99%